Molding of orofacial structures through pre-surgical orthopedics in patient with cleft lip and palate: A case report - Gómez España, Daniela (2022)
The cleft lip and palate is a congenital craniofacial malformation produced by the lack of fusion of the medial nasal processes and maxillary processes during the first weeks of embryonic development. The main objective of this clinical case was to mold and shape orofacial structures through presurgical orthopedics in a patient with cleft lip palatine. The results were obtained by placing the Bilateral Nasoalveolar Shaper, improving feeding and lingual position; Furthermore, after 4 months of use, the palatal segments were reduced, decreasing from 12.92mm to 9.15mm in width, modeling of the nasal cartilages, columella formation from 0 to 5mm and projection of the tip of the nose.